Węgiel brunatny - czy będzie polskim surowcem energetycznym xxi wieku? = Brown coal - can it be polish energy resource for the XXIst century? - Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Brown coal is used for energy, whose resources are counted in Poland for 100-300 years of operation assuming current share in the energy mix. Polish government economic plans involve intensification of economic development using own energy sources. Energy from renewable and other sources will also be required as part of the mix.
Keywords: węgiel brunatny; Gubin; Brody; energetyka węglowa; rekultywacja terenów powydobywczych; lignite; brown-coal energy; post-mining areas reclamation